Examining the Mediating Role of Body Esteem in the Relationship Between Social Body Anxiety and Health-Oriented Lifestyle in Women with Obesity - Hajiebrahim Araghi , Bita; Rahmani, Mohammad Ali; Rahimaghaee , Flora (Psychology of Woman Journal, 2024)
Objective: The aim of this study was to examine the mediating role of body esteem in the relationship between social body anxiety and a health-oriented lifestyle in women with obesity. Methods and Materials: The present study is applied in nature and belongs to the category of correlational designs, specifically structural equation modeling. The statistical population consisted of all women with obesity who visited obesity and beauty clinics in various regions of Tehran in 2023. The sample size was determined using Stevens’ (1996) sample estimation method, with a total of 250 participants considered. Data were collected using the Health-Promoting Lifestyle Profile (HPLP) by Walker et al. (1987), the Social Physique Anxiety Scale by Hart et al. (1989), and the Body Esteem Scale by Mendelson et al. (2001). Data analysis was conducted using SPSS version 26 and AMOS version 24. Findings: Pearson correlation results showed a significant relationship between social body anxiety, body esteem, and a health-oriented lifestyle. The results also indicated that social anxiety (β = -0.202, P = 0.033) had a significant negative effect on a health-oriented lifestyle, and body esteem (β = 0.285, P = 0.011) had a significant positive effect on a health-oriented lifestyle. Social anxiety (β = -0.379, P < 0.001) had a significant negative effect on body esteem. Additionally, the results showed that body esteem plays a mediating role in the relationship between social body anxiety and a health-oriented lifestyle in women with obesity, with an indirect effect of -0.1102. Conclusion: Overall, the results indicate that body esteem significantly mediates this relationship. Specifically, social anxiety can impact a health-oriented lifestyle through its effect on body esteem. This suggests that changes in body esteem can alter the way social anxiety affects a health-oriented lifestyle. The negative indirect effect suggests that the relationship between social anxiety and a health-oriented lifestyle is inversely influenced by body esteem.